Broken windows in the cul-de-sac?: race/ethnicity and quality-of-life policing in the changing suburbs - Beck, Brenden (Crime & delinquency, 2019)
The racially disparate impacts of the carceral state are well studied, but most of the research has focused on large cities. Are suburban and urban policing similar? One trend suggests suburban policing might be in flux: U.S. suburbs underwent a dramatic demographic shift between 1990 and 2014. Their White populations declined sharply and their poor, non-White, and foreign-born populations all grew. During the same time, broken windows policing, with its aggressive enforcement of low-level quality-of-life crimes, gained popularity. Are suburban police departments adopting broken windows strategies or making racially disproportionate arrests in response to recent racial and economic changes? I use panel data (N = 1,038 suburbs and 50 cities, with eight observations 1990 to 2014) in fixed effects regression models to address these questions. Data are compiled from the Uniform Crime Reporting Program and the Census. Descriptive statistics show that while quality-of-life arrests are down overall, the White–Black disparity in suburban arrests remains extreme, especially in mostly White suburbs. Multivariate models indicate that increases in poor people in a suburb are associated with increases in quality-of-life arrests, while more Hispanic people are associated with fewer arrests. Results suggest that urban and suburban policing dynamics are quite different.